A Case of Cystic Adventitial Degeneration of the Left Popliteal Artery Diagnosed by Intravascular Ultrasound - Takeshi Niizeki; Mitsunori Ishino; Tatsuro Kitahara; So Yamauchi; Eiichiro Ikeno; Isao Kubota (Clinical Medicine Insights: Case Reports, 2016)
An 87-year-old male was admitted with intermittent claudication of the left calf. We performed lower extremity angiography, which revealed stenosis of the left popliteal artery. Intravascular ultrasound (IVUS) image correctly identified the cystic appearance of visualized extravascular hypodensity, causing extrinsic compression of the lumen. We diagnosed the condition as cystic adventitial degeneration (CAD) of the popliteal artery. We operated a resection of a cyst with the artery and replaced the autovein graft (saphenous vein). After surgery, the patient was free of symptoms. CAD is a rare disease; thus, our IVUS findings may provide unique diagnostic clues in patients with CAD.